Thiomonas sp. CB2 is able to degrade urea and promote toxic metal precipitation in acid mine drainage waters supplemented with urea - Farasin, Julien; Andres, Jérémy; Casiot, Corinne; Barbe, Valérie; Faerber, Jacques; Halter, David; Heintz, Dimitri; Koechler, Sandrine; Lièvremont, Didier; Lugan, Raphael; Marchal, Marie; Plewniak, Frédéric; et al. (Frontiers in Microbiology, 2015)
The acid mine drainage (AMD) in Carnoulès (France) is characterized by the presence of toxic metals such as arsenic. Several bacterial strains belonging to the Thiomonas genus, which were isolated from this AMD, are able to withstand these conditions. Their genomes carry several genomic islands (GEIs), which are known to be potentially advantageous in some particular ecological niches. This study focused on the role of the “urea island” present in the Thiomonas CB2 strain, which carry the genes involved in urea degradation processes. First, genomic comparisons showed that the genome of Thiomonas sp. CB2, which is able to degrade urea, contains a urea genomic island which is incomplete in the genome of other strains showing no urease activity. The urease activity of Thiomonas sp. CB2 enabled this bacterium to maintain a neutral pH in cell cultures in vitro and prevented the occurrence of cell death during the growth of the bacterium in a chemically defined medium. In AMD water supplemented with urea, the degradation of urea promotes iron, aluminium and arsenic precipitation. Our data show that ureC was expressed in situ, which suggests that the ability to degrade urea may be expressed in some Thiomonas strains in AMD, and that this urease activity may contribute to their survival in contaminated environments.